Multi-environment evaluation of rice genotypes: Impact of weather and culm biochemical parameters against sheath blight infection - Panda, S.; Naveen kumar, R.; Pavani, S.L.; Ganesan, S.; Singh, P.K.; Sah, R.P.; Varijakshapanicker, Padmakumar; Subudhi, H.; Mahender, A.; Anandan, A.; Ali, J. (Frontiers Media, 2023)
Introduction: Sheath blight caused by Rhizoctonia solani is one of the major diseases of rice, causing widespread crop losses. The use of semi-dwarf rice varieties in the ongoing nutrient-intensive rice cultivation system has further accentuated the incidence of the disease. An ideal solution to this problem would be identifying a stable sheath blight-tolerant genotype.